P050 Clinical outcomes of refractory Crohn's disease following hematopoietic stem cell transplantation: A single center experience. (July 2019) - Natália, Queiroz; Luisa, Barros; Matheus, Azevedo; Alexandre, Carlos; Luciane, Milani; Beatriz, Rocha; Jane, Oba; André, Leite; Aytan, Sipahi; Adérson, Damião
Abstract : BACKGROUND: Hematopoietic stem cell transplantation (HSCT) has recently been described as an option for treatment of patients with refractory Crohn's disease in whom surgical treatment is not possible or desired (1 ). However, the reported long term follow up of patients submitted to this treatment is usually no longer than12 months (2 ). METHODS: Data from 5 patients who had undergone HSCT due to refractory Crohn's disease followed in the IBD unit of Gastroenterology Division of the Clinics Hospital of the University of São Paulo was retrospectively collected based on medical records. RESULTS: From 2014 to 2016, 5 patients were transplanted: 4 male and one female. Median age was 27 years old [20–43] and mean disease duration was 6 years [3–8]. Two of them were active smokers. Location of disease was ileocolonic in 4 patients and colonic in the other. Three of them had inflammatory behavior, one stricturing and the other penetrating disease (perianal fistula). One patient had had previous right colectomy before HSCT. All patients had failed at least one immunosuppressor (Azathioprine and/or Methotrexate) and 2 anti-TNFs (Infliximab and Adalimumab). Only one patient was treated with anti-integrin (Vedolizumab) prior to HSCT. Patients underwent annual lower GI endoscopies after transplantation during a 36-month median follow-up. After HSCT, all patients had clinical remission for at least 6 months. Endoscopic remission (defined by absent of ulcers) was observed in only one patient in the first year. This patient was non smoker, had colonic inflammatory disease and no surgical history. Four patients relapsed during the first year and required retreatment with immunomodulator and/or anti-TNF. Half of them (n = 2) achieved deep remission after 36 months of follow up. None required surgery or died after HSTC. CONCLUSION(S): This long term follow-up case series have demonstrated that HSCT may be a reasonable option to very refractory CD patients in order to avoid radical surgical procedures. Even when endoscopic remission is not obtained after transplantation, refractory patients can become responders to medications previously used.